Investigation of applicability of immobilization in calcium alginate gel - Yamada, Ryuhei; Tanaka, Takanori; Jami, Mohammed Saedi; Iwata, Masashi (2014)
Natural polymers such as sodium alginate (Na-Alg) are used as agglomerating agents in the water clarification process due to their harmlessness. Alginic acid is an intercellular substance found in brown alga. It comprises a mannuronic acid block, a glucronic acid block, and the block in which mannuronic acid and glucronic acid are alternately connected. Alginic acid molecules are cross-linked by a divalent metal ion such as Ca2+, and forms gel. For the quick dewatering of muddy water, a new method utilizing particle immobilization in calcium alginate gel has been developed and is in practical use. In this study, the applicability of this treatment method is investigated with respect to the following binary systems: suspension, o/w emulsion and polymer solution.